Navigating the digital beat: a review of social media as a public engagement tool in policing - Ralph, Liam; Elliott, Ian C.; Murphy, Joanne; Glennon, Russ (International journal of emergency services, 2024)
PurposeThis article explores the changing nature of social media use as a public engagement tool by police services.Design/methodology/approachA comprehensive review is conducted of academic studies from criminology and policing journals. Sources are identified from key academic databases and are analysed in relation to three decades (2000–2009, 2010–2019 and 2020 to present) to show how the use of social media has changed over time.FindingsThe way in which social media is used in policing has changed considerably over time. From initial enthusiasm, it is found that there is growing scepticism in the use of social media as a public engagement tool. After an initial proliferation in use, there is then increasing consolidation and control in response to concerns about reputational risk.Research limitations/implicationsThe research highlights underlying dynamics of engagement and retrenchment, which offer important insights for how we understand public engagement and value creation in policing and emergency services more generally. We draw on academic research from English-language academic journals, but we have endeavoured to include research from the broadest possible range of countries.Practical implicationsThis study demonstrates how the police and other public services must respond to the growing use of social media by the public to maximise value creation whilst minimising the threats that come from potential value destruction.Originality/valueThis study is the first to comprehensively review the policing and criminology literature related to social media and to apply a public engagement lens to this analysis.